Availability Analysis of Selected Mining Machinery Using Industrial Automation Systems - Jarosław BRODNY (Communications of International Proceedings, 2021)
With regard to underground hard coal production, mechanical approach in both the excavation process and underground transport is of key importance. Currently, this process is carried out with the use of highly efficient mechanized longwall complexes. The classic longwall system consists of a mining machine (shearer or plough), drag chain conveyors (armored face conveyor and beam stage loader), a crusher, and mechanized longwall supports. The high cost of these machines makes mining companies strive to use them as efficiently as possible. This efficiency, according to the Overall Equipment Effectiveness (OEE) model, is regarded as the availability of these machines. Therefore, to achieve a high degree of their availability, it is necessary to monitor their work both objectively and effectively. The article presents the developed method of using industrial automation systems and IT solutions to analyze the availability of selected mining machinery. The research involved a longwall shearer, drag chain conveyors (armored face conveyor and beam stage loader) and a crusher. The time series analysis of the diagnostic parameters of these machines was used to determine their availability. These parameters were collected in a data warehouse and involved the position and speed of the longwall shearer, as well as the temporal current waveforms consumed by the engines of the conveyors and the crusher. On this basis, the actual operation times of these machines were determined and compared to the normative times. The results obtained are of great significance for the research on the effectiveness of the production process, as they enable an ongoing assessment of the operation of these machines and possible corrections in the event of any interruptions. The developed method and applied IT solutions based on data from the industrial automation system made it possible to obtain reliable and employee-independent information on the operation of studied machinery. This information can be used to support the process of managing the operation of these machines and improve their efficiency. The study showed that the designated availability of selected machines is at a low level, which indicates the need to monitor their work, identify causes and implement necessary changes.
Keywords: Machine Availability; Mining Machinery Production Efficiency; Mining Operation; Databases; Industrial Automation; OEE Model.